Solidarity, Resistance and Transformation: Intellectual Struggles in an Era of Diaspora and Empire - Ruiz, Lester Edwin J. (Silliman Journal, 2023)
This essay explores the struggles that confront intellectuals and other producers of knowledge in an era of massive transnational, transborder movement of peoples in Diaspora, at a time characterized by overt or subtle forms of neo-colonial domination. The paper assembles a vast array of readings and examines a host of themes not so much to understand the experiences of those who are in Diaspora as to locate the place and define the role of intellectuals in grappling with strangeness and turbulence brought about by the experience of exile and the continuing process of imperial suppressions. Proceeding from a postcolonial perspective, the paper identifies five instances, called ruptures, of the continuing process of resistance and reconstruction that intellectuals have used to challenge influential master discourses as well as the grand narratives of modernity. At the same time, the paper exposes the inherent contradiction involved in such projects. This paradoxical situation includes practices, conceptions, and actions which are, unwittingly, complicit with the imperial enterprise and mask—even perpetuate—unequal economic and cultural relations. Called repetitionin this paper, this situation simply reproduces the inequalities of imperial power relations at the level of the production, reproduction, and re-presentation of knowledge. The essay sees the challenge of the intellectual as one fraught not just with struggle but also with hope, with resistance but also in solidarity with those sharing a similar fate in order to transform a fragmented, at once alien and alienating world into a "radically-inclusive community." While recognizing the ambivalent, complex, and processual nature of both diasporic experience and imperial relations, the paper concludes that what is important is not how difference can be overcome, but rather how and under what conditions it is possible for people not only to live together, but to live together well.